1927
DOI: 10.1084/jem.45.5.865
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Poisoning in Cold Blooded Animals

Abstract: 1. Exposure of frogs to atmospheres containing approximately 95 per cent of oxygen is without apparent effect on their state of well being, and produces no noticeable changes in the appearance of their web capillaries. 2. Turtles exposed to similar atmospheres are also apparently unaffected unless the oxygen be warmed to mammalian temperature. 3. At this temperature (37.5°C.) the turtles behave like mammals, showing loss of appetite, shortness of breath, death and, at autopsy, hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1928
1928
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…11 Experiments over the first part of the last century revealed that younger animals were relatively “resistant” to the toxic effects of oxygen when compared to their adult counterparts. This was true for turtles, 12 rats, 13 fruit flies, 14 and cats. 15 In 1957, it was noted that neonatal rats were resistant to oxygen toxicity.…”
Section: The Response To Oxidative Stress Varies Across Development Amentioning
confidence: 83%
“…11 Experiments over the first part of the last century revealed that younger animals were relatively “resistant” to the toxic effects of oxygen when compared to their adult counterparts. This was true for turtles, 12 rats, 13 fruit flies, 14 and cats. 15 In 1957, it was noted that neonatal rats were resistant to oxygen toxicity.…”
Section: The Response To Oxidative Stress Varies Across Development Amentioning
confidence: 83%
“…The skin of X. laevis normally absorbs oxygen from water with a DO concentration of 6–7 mg/L; thus, some parts of the body surface exposed to air in reoxygenation may be exposed to hyperoxia. Although hyperoxia exposure is generally associated with tissue injury, frog was reported to show no noticeable changes in the lungs and other tissues after long‐term chronic exposure to hyperoxia (i.e., above 90% O 2 at room temperature) (Faulkner & Binger, 1927). Therefore, the tissue injury observed in this study may be attributed to oxidative stress due to intermittent hypoxic exposure rather than due to hyperoxic exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that fatal cases apparently less often reach a saturation of 90 per cent in the chamber than those which survive, difficult and expensive to maintain when there is frequent ingress and egress from the chamber as there must be in caring for a sick patient, partly because it does not seem wise to approach too closely the toxic concentration of oxygen in the presence of an already damaged lung and elevated temperature (14). The division of these cases into two groups, one which recovered and one which succumbed, is perhaps not a logical one, but it is convenient.…”
Section: Methodsmentioning
confidence: 99%